2006
DOI: 10.1038/emm.2006.2
|View full text |Cite
|
Sign up to set email alerts
|

Activation of the intrinsic mitochondrial apoptotic pathway in swine influenza virus-mediated cell death

Abstract: The mitochondrial pathway of swine influenza virus (SIV)-induced apoptosis was investigated using porcine kidney (PK-15) cells, swine testicle (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
11
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 25 publications
1
11
0
Order By: Relevance
“…Several studies have reported that Bcl-2 modulates cell differentiation (Lu et al, 1995) and gene expression (Miyashita et al, 1995) and also regulates the transactivity of several transcription factors such as NF-κB (Ricca et al, 2000), and p53 (Froesch et al,199). Furthermore Bcl-2 regulates outer mitochondrial membrane permeability and release of cytochrome C and other apoptogenic factors (Huang and Strasser, 2000;Adams and Cory, 2001;Newmeyer and Ferguson-Miller, 2003;Tsujimoto, 2003;Choi et al, 2006). Previously, we reported that PA produced by PLD raises Bcl-2 protein expression in several cells lines (Oh et al, 2007;Cho et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have reported that Bcl-2 modulates cell differentiation (Lu et al, 1995) and gene expression (Miyashita et al, 1995) and also regulates the transactivity of several transcription factors such as NF-κB (Ricca et al, 2000), and p53 (Froesch et al,199). Furthermore Bcl-2 regulates outer mitochondrial membrane permeability and release of cytochrome C and other apoptogenic factors (Huang and Strasser, 2000;Adams and Cory, 2001;Newmeyer and Ferguson-Miller, 2003;Tsujimoto, 2003;Choi et al, 2006). Previously, we reported that PA produced by PLD raises Bcl-2 protein expression in several cells lines (Oh et al, 2007;Cho et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Members of the Bcl-2 family are classified as antiapoptotic factors, which include Bcl-2, Bcl-xL, Mcl-1, and others. The proapoptotic members can be separated into two subgroups: the Bax subfamily (Bax, Bak and Bok), which contain multiple BH domains, and the BH3-only family including Bad, Bid, Bim, Noxa, Hrk, and others (Huang and Strasser, 2000;Adams and Cory, 2001;Newmeyer and Ferguson-Miller, 2003;Tsujimoto, 2003;Choi et al, 2006). Bcl-2 protein is the most important regulator of apoptosis and is involved in the regulation of the cell cycle (O'Reilly et al, 1997), prolongs cell survival (Korsmeyer, 1992), and inhibits apoptosis (O'Reilly et al, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…While several of the isolates tested showed a significantly enhanced ability to induce apoptosis compared to that after treatment with gemcitabine and cisplatin, the H7N3 isolate repeatedly outperformed the others in terms of the rapidity and potency of cell death induced. Strain-specific variations in apoptotic induction have previously been documented in primary cultures and established cell lines in the cases of human, avian, and swine influenza viruses (36,37). The particularity of the H7N3 isolate led us to investigate it further; we examined the specific apoptotic pathway induced in a highly sensitive cell line (BxPC-3) compared to that of a resistant line (HPDE6).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, although the pancreas is not considered a typical site of replication after standard infection, influenza A virus seems to be capable of infecting and damaging pancreatic cells in severe infections. Furthermore, the fact that IAV is known to induce apoptosis in numerous cell types (35)(36)(37) may provide an advantage in overcoming the known resistance to apoptosis of PDA cells.…”
mentioning
confidence: 99%
“…Immunoprecipitation was performed as follows (29). After homogenizing liver tissue with 1 ml of lysis buffer (pH 7.5, 50 M Tris-HCl, 150 M NaCl, 1 M MgCl 2 , 1 M CaCl 2 , 1 M sodium orthovanadate, 100 M NaF, 1 M EGTA, 1% Triton X-100, 10% glycerol, leupeptin (5 µg/ml) and 1 mmol/l phenylmethylsulfonyl fluoride) on ice, it was washed twice with ice-cold PBS.…”
Section: Methodsmentioning
confidence: 99%